Correlation between Low Birth Weigth and Stunting in Children Under Five: Meta Analysis - Ode, Diana; Murti, Bhisma; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2022)
Background: Stunting in children is a risk factor for increasing child mortality. The purpose of this study was to determine the relationship between LBW and the incidence of stunting based on previous primary studies. Subjects and Method: This research was conducted using a meta-analysis study with PICO as follows: P = toddler, I = low birth weight, C = normal birth weight, O = stunting. Search articles in this study using 3 databases, namely Pubmed, Google Scholar and Springerlink. Search articles using the following keywords: Low birth weight AND Stunted OR Birth weight AND Stunted, articles were analyzed using the Review Manager 5.3 application. Results: There are 11 articles from Rwanda, Nepal, Ethiopia, Eastern Kenya, Pakistan, China, Indonesia, and Tanzania from 2017-2022 which were analyzed using PRISMA flow diagrams. The results of this study indicate that toddlers who have a history of being born with low birth weight have a risk of experiencing stunting as much as 2.19 times compared to toddlers who have a history of birth with normal birth weight (aOR= 2.19; 95% CI= 1.77 to 2.69; p<0.001). Conclusion: Toddlers with a history of LBW births are at risk for stunting. Keywords: LBW, stunting, toddlers, meta-analysis. Correspondence: Diana Ode. Master’s Program in Public Health, Universitas Sebelas Maret. Jl.Lawu raya Seturan Caturtunggal Depok Sleman Yogyakarta 55281 Indonesia. Email: dianaodef161@gmail.com. Mobile: +6285395912173.